2007
DOI: 10.1002/nml.170
|View full text |Cite
|
Sign up to set email alerts
|

The role of social anxiety in volunteering

Abstract: Volunteer management literature suggests that the most effective means of recruitment is personal asking. However, agencies that apply this method do not report the "expected" success in volunteer recruitment. Often they face the volunteer recruitment fallacy, i.e., the situation in which those people assumed to be interested in volunteering do not necessarily volunteer. Based on the literature of shyness or "social anxiety" and on empirical observations, this paper suggests that social anxiety often deters ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…The price axis moves between high costs versus low costs attached to the volunteering experience. The literature indicates three major costs related to volunteering: (1) less available time and a feeling that volunteering takes more time than expected (Blake and Jefferson, 1992;Omoto and Snyder, 1993), (2) stigma and negative social reaction, due to working with controversial organizations or populations (such as AIDS patients or anti-governmental organizations; Omoto and Snyder, 1993), and (3) psychological difficulties like burnout, secondary trauma, stress, and despair (Cyr and Doerick, 1991;Capner and Caltabiano, 1993;Mitchell et al, 2004) or the social anxiety that may be attached to starting a new volunteer role (Handy and Cnaan, 2007). As Chinman and Wandersman (1999) showed, costs and benefits are also related to the kind of organization and role the volunteers undertake.…”
Section: Prices and Costs Of Volunteering: Low Versus Highmentioning
confidence: 97%
See 1 more Smart Citation
“…The price axis moves between high costs versus low costs attached to the volunteering experience. The literature indicates three major costs related to volunteering: (1) less available time and a feeling that volunteering takes more time than expected (Blake and Jefferson, 1992;Omoto and Snyder, 1993), (2) stigma and negative social reaction, due to working with controversial organizations or populations (such as AIDS patients or anti-governmental organizations; Omoto and Snyder, 1993), and (3) psychological difficulties like burnout, secondary trauma, stress, and despair (Cyr and Doerick, 1991;Capner and Caltabiano, 1993;Mitchell et al, 2004) or the social anxiety that may be attached to starting a new volunteer role (Handy and Cnaan, 2007). As Chinman and Wandersman (1999) showed, costs and benefits are also related to the kind of organization and role the volunteers undertake.…”
Section: Prices and Costs Of Volunteering: Low Versus Highmentioning
confidence: 97%
“…As Meijs et al (2006aMeijs et al ( , 2006b showed, volunteerability can be manipulated from both the supply side (e.g., when volunteers follow a specific training in order to perform certain tasks) as well as from the demand side (e.g., when organizations change assignments in order to fit the current skills of volunteers). But even if the fit between individual supply and organizational demand is perfect, other obstacle may arise, such as social anxiety, which may prevent potential volunteers from coming forward (Handy and Cnaan, 2007).…”
Section: Volunteerability and Recruitabilitymentioning
confidence: 99%
“…Anxiety in general was found to be negatively related with prosocial behavior (Eisenberg et al 2006). Handy and Cnaan (2007) found that people with higher levels of social anxiety are less willing to volunteer (Handy and Cnaan, 2007). The idea was also supported with novel findings in the field of social neuroscience.…”
Section: Uncertainty Avoidance and Prosocial Behaviormentioning
confidence: 60%
“…For many organizations, the Internet has been a successful way of attracting volunteers who have not responded to the usual recruitment methods of volunteering. This applies in particular to those introverted individuals who may hesitate to get involved because of social anxiety about going to new places and working among strangers (Handy and Cnaan 2007), to the disabled, or to those who lack transportation. Thus, virtual volunteering has presented many opportunities to those who want to volunteer without having to leave the comfort of their homes and to those who want flexibility in their volunteer hours.…”
Section: Trends In Volunteeringmentioning
confidence: 94%